Intra-structural processes of accounting and financial results control as a tool for improving the efficiency of accounts receivable management - A. V. Fedorov; T. M. Rogulenko (Управление)
The article deals with the organization and implementation of intra-structural processes of accounting and control of financial results as a tool to improve the efficiency of accounts receivable management at pharmaceutical enterprises. In order to meet the requirements of the market for the quality of products, the management needs not only to increase the level of manufacturability of production, but also to solve the issues of improving the efficiency of enterprise management aimed at achieving the planned values of financial results. A key role in choosing a management decision is played by the organization of mechanisms for collecting, processing and storing production information at the enterprise, the development of algorithms for accounting and control of enterprise performance indicators. The availability of systematized information sources at the enterprise serves as a justification for the choice of a particular management strategy. The achievement of the tasks set by the management of the enterprise is ensured not only by the quality of managerial decision-making, but also by the introduction of mechanisms of internal accounting and control processes. The authors substantiate the importance of accounts receivable management in building effective enterprise management and achieving the greatest efficiency of the enterprise. Special attention in the article is paid to the importance of accounting and management accounting, as well as control of key parameters of the company’s activities, which allow to identify the causes of deviations of actual parameters from the basic ones and to develop recommendations for adjusting the implemented control influence on the internal processes of the enterprise. According to the authors, the considered mechanism for building and organizing the functioning of intra-structural processes for accounting and controlling financial results ensures the adoption of operational management decisions, the timely identification and leveling of deviations, which makes it possible to overcome crisis situations and minimize the negative impact of external and internal factors on the enterprise.